Formação de profissionais para a atenção a saúde de deficientes auditivos - Verônica Francisqueti Marquete; Luiz Gonzalez Conelheiro Junior; Heloá Christinelli; Élen Ferraz Teston; Gabriella Michel dos Santos Benedetti; Maria Antonia Ramos Costa (Universidade Federal de Santa Maria, 2018)
Aim: to know the perception of the academics of the courses of the health area on their training to assist the hearing impaired people. Method: exploratory descriptive research with a qualitative approach. The data were collected through a questionnaire, prepared by the researchers, with the nursing and physical education students of a public university in the Paraná countryside, enrolled in the 4th year of their course in 2016 and analyzed by the content analysis technique. The collection period was from November 2016 to February 2017. Results: Forty-two students participated in the study. The analysis resulted in the thematic axis: challenges experienced in training for the care of hearing impaired individuals. Final considerations: the emergence of the need for higher education institutions to create strategies to sensitize students to the importance of this learning and to provide quality training, seeking to effectively enable them to communicate and care for the hearing impaired people.